Paradigma Surat Tanda Bukti Akta Keterangan Waris Sebagai Asas Kepastian Hukum - Lia Gulianti (Jurnal USM Law Review)
This study aims to examine the effect of Permen ATR / BPN Number 16 of 2021 concerning the third amendment to Land Registration in Article 111 paragraph (1) letter C concerning the making of a certificate of evidence of the Deed of Inheritance and Article 111 paragraph (5) the transfer of rights falls to 1 (one) person who receives the inheritance based on the Deed of Inheritance, which deed raises inconsistencies in legal norms related to Article 111 paragraph (1). This research focuses on normative juridical law as formulated by legislation. The inheritance certificate is made before a notary for all groups and the inheritance deed is made the same as the Deed of Distribution of Inheritance Rights which has a different form and content, The fact in the field is that there are many Notaries who cannot distinguish the making of the deed which results in a discrepancy between the evidence letter of the Deed of Inheritance and the Deed of Distribution of Inheritance, the deed is recorded at the Land Agency Office in various regions such as Bandung City, Bandung Regency and West Bandung, resulting in legal uncertainty and resulting in confusion or obscuration of rules and having an impact on heirs and sole recipients or recipients of inheritance rights that can be cancelled. As there is an abolition of groups but cannot be abolished, the pluralism inheritance law, so it is necessary to have regulations governing the Deed of Inheritance Certificate and Deed of Division of Inheritance Rights due to different functions. As with legislation, there is a legal principle that regulations that have a lower level in the hierarchy of regulations do not differ from each other.